Jorvik: A membrane-containing phage that will likely found a new family within Vinavirales - Pavol Bárdy; Conor I.W. MacDonald; Roman Pantůček; Alfred A. Antson; Paul C.M. Fogg (iScience, 2023)
Summary: Although membrane-containing dsDNA bacterial viruses are some of the most prevalent predators in aquatic environments, we know little about how they function due to their intractability in the laboratory. Here, we have identified and thoroughly characterized a new type of membrane-containing bacteriophage, Jorvik, that infects the freshwater mixotrophic model bacterium Rhodobacter capsulatus. Jorvik is extremely virulent, can persist in the host integrated into the RuBisCo operon and encodes two experimentally verified cell wall hydrolases. Jorvik-like prophages are abundant in the genomes of Alphaproteobacteria, are distantly related to known viruses of the class Tectiliviricetes, and we propose they should be classified as a new family. Crucially, we demonstrate how widely used phage manipulation methods should be adjusted to prevent loss of virus infectivity. Our thorough characterization of environmental phage Jorvik provides important experimental insights about phage diversity and interactions in microbial communities that are often unexplored in common metagenomic analyses.